Microstructural development on AISI 1060 steel by FeW/B4C composite coating produced by using tungsten inert gas (TIG) process - Islak, Serkan; Buytoz, Soner; Karagoz, Muzaffer (Natl Inst Science Communication-Niscair, 2012)
This study discusses the effects of B4C addition on the morphologies of primary carbides and eutectic colonies in FeW weld-surfacing alloys. Results reveal that a series of FeW weld-surfacing alloys with different B4C contents are successfully fabricated onto AISI 1060 steel by using tungsten inert gas (TIG) arc welding. SEM observations show that the obtained coating sheet has a smooth and uniform surface, as well as a metallurgical combination with the AISI 1060 steel substrate without cracks and pores at the interface. Fe-23(C,8)(6), Fe-3(C,B), FeW2B2 and FeW3C boride and carbides are determined in the microstructure. The microhardness values of the coating results show a difference depending on the rate of B4C and coating conditions. The maximum microhardness value of the coating is about 1095 HV.
Keywords: TIG process; Composite coatings; Microstructure